On the involvement of History and Philosophy of Science in teaching Science - an approach promoting cultural content knowledge - IGAL GALILI (Metaichmio Publications, 2015)
This study addresses the approach of representing physics knowledge as being comprised of few fundamental theories, each explicitly structured. Instead of a regular dual disciplinary structure, nucleus and body of knowledge, we expand to the third type of knowledge elements - periphery. The latter includes alternatives and problematic elements of knowledge from the historical discourse in the particular domain of knowledge. The inclusion of alternatives not only contrasts the nucleus of the theory but actually determines its meaning and the area of its validity. The periphery may include alternative conceptions of learners. It is the periphery that establishes the space of learning by conceptual variation which is required for meaningful learning. Altogether, this teaching approach seeks constructing cultural content knowledge (CCK) in the learner. Moreover, CCK determines the role and contribution of the history and philosophy of science in science curriculum as providing elements to the triadic structure and clarifying the relationship among the fundamental theories of physics. The CCK is exemplified with regard to the concept of weight.